WDM Networks: Contention Resolution, Amplified Spontaneous Emission Noise And Four-Wave Mixing Aware Routing And Wavelength Assignment - Tan, Saw Chin (2008)
Routing and Wavelength Assingnment (RWA) in WDM packet switched networks is studied in this research project. The focus is on slotted(synchronous) optical packet switching (OPS) networks where the packets have a fixed size and are synchronized before entering the switch. Three main problems are addressed: packet contention resolution in OPS and RWA in the absence and presence of physical impairments.